Rising CO2 drives divergence in water use efficiency of evergreen and deciduous plants - Yiotis, Charilaos; Mc Elwain, Jennifer (American Association for the Advancement of Science (AAAS), 2019)
Intrinsic water use efficiency (iWUE), defined as the ratio of photosynthesis to stomatal conductance, is a key variable in plant physiology and ecology. Yet, how rising atmospheric CO2 concentration affects iWUE at broad species and ecosystem scales is poorly understood. In a field-based study of 244 woody angiosperm species across eight biomes over the past 25 years of increasing atmospheric CO2 (~45 ppm), we show that iWUE in evergreen species has increased more rapidly than in deciduous species. Specifically, the difference in iWUE gain between evergreen and deciduous taxa diverges along a mean annual temperature gradient from tropical to boreal forests and follows similar observed trends in leaf functional traits such as leaf mass per area. Synthesis of multiple lines of evidence supports our findings. This study provides timely insights into the impact of Anthropocene climate change on forest ecosystems and will aid the development of next-generation trait-based vegetation models.
PUBLISHED
Keywords: tropical to boreal forests; intrinsic water use efficiency (iWUE); stomatal conductance